Ibrutinib protects against acute lung injury via inhibiting NLRP3/Caspase-1 in septic mice model. (December 2022) - Tang, Huiming; Li, Hui; Yang, Yang; Tang, Manli; Li, Zhanfei; Bai, Xiangjun; Wang, Yuchang
Abstract: Acute lung injury is a severe complication of sepsis with high mortality in ICU. Increasing evidences have showed that Ibrutinib, a Bruton's Tyrosine kinase inhibitor, plays a critical role in numerous inflammation-related diseases. However, its therapeutic effect and mechanism in sepsis induced acute lung injury remain unclear. In this study, cecal ligation puncture (CLP) was performed on male C57BL/6 J mice to establish a mouse model of sepsis. Ibrutinib (50 mg/kg/d) was administered by gavage 1 day before CLP, once a day, for 3 consecutive days. on the fourth day mice were given one dose of ibrutinib 2 h before CLP induction, and another dose was given 24 h later. Histopathological examination of lung tissues was performed at 72 h. The levels of myeloperoxidase (MPO), interleukin (IL)− 6, TNF-α, IL-1β and IL-18 in bronchoalveolar lavage fluid (BALF) were determined by ELISA. Western blotting was used to detect the expression of pyroptosis related proteins. The results showed that Ibrutinib treatment significantly improved the prognosis of mice and mitigated the lung histopathological injury and inflammatory response. Moreover, Ibrutinib significantly inhibited the expression of pyroptosis related proteins (NLRP3, Caspase-1, Gasdermin D (GSDMD), IL-1β and IL-18) in the lung tissues of sepsis mice. In conclusion, our results suggest that Ibrutinib exerted protective effects against lung injury of septic mice and inhibited the activation of pyroptosis in lung tissue, which may be a potential treatment for sepsis induced lung injury. Highlights: Ibrutinib protects septic mice and attenuates sepsis induced ALI. Ibrutinib inhibits lung inflammation and inflammatory cells infiltration in lung tissues of septic mice. Ibrutinib downregulates pyroptosis related proteins in lung tissue of septic mice